On flexural properties of additive manufactured composites: Experimental, and numerical study. (8th February 2022) - Krzikalla, David; Měsíček, Jakub; Halama, Radim; Hajnyš, Jiří; Pagáč, Marek; Čegan, Tomáš; Petrů, Jana
Abstract: Components prepared by additive technologies are increasingly utilized because of shape freedom and new possibilities of fibre reinforcing. Therefore, it is important to investigate the mechanical properties and possibilities of numerical simulations of theirs. This study is focused on the experimental and numerical examination of the flexural properties of FDM long carbon fibre reinforced composites with polymeric matrix of Onyx by 3-point bending test. Two fibre volumetric contents and two reinforced layer distributions were investigated. The experiments served also as case studies for the verification of numerical models. Four types of finite element models were proposed and examined. Analytical and RVE homogenisation methods were utilized. Except the flexural properties obtained, the results suggested that the reinforced layer distribution is crucial over the fibre content. Both homogenisation methods showed comparable longitudinal material constants but very dissimilar shear and transversal constants. Nonetheless, the results suggested that the influence of transversal constants can be negligible under certain stress states. Layered shell element model and solid element model reinforced by trusses showed excellent accuracy with respect to the experiments. Optical microscopy confirmed the correct distribution of the reinforced fibres and revealed the real structure of the printed composites. Graphical abstract: Image 1 Highlights: Flexural properties of FDM long carbon fibre reinforced composites investigated. Reinforcement distribution found to be more important than fibre volumetric ratio. FEM models of layered shell or solid reinforced by links element found as accurate. Shear and transversal constants have minor influence on the results under certain stress states. Optical microscopy revealed the internal composite structure.